2009
DOI: 10.1111/j.1600-0854.2008.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensing, Signaling and Sorting Events in Kidney Epithelial Cell Physiology

Abstract: The kidney regulates body fluid, ion and acid/base homeostasis through the interaction of a host of channels, transporters and pumps within specific tubule segments, specific cell types and specific plasma membrane domains. Furthermore, renal epithelial cells have adapted to function in an often unique and challenging environment that includes high medullary osmolality, acidic pHs, variable blood flow and constantly changing apical and basolateral 'bathing' solutions. In this review, we focus on selected prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 84 publications
0
42
0
Order By: Relevance
“…[3][4][5][6][7]18 We found that GPR4 mRNA is expressed in the kidney collecting duct, the nephron segment responsible for net acid excretion and final adjustments of the acid-base homeostasis. Cultured collecting duct cells (mOMCD1), which express GPR4 mRNA endogenously, exhibit pH-dependent accumulation of intra- Blood samples were obtained from the tail artery in conscious mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7]18 We found that GPR4 mRNA is expressed in the kidney collecting duct, the nephron segment responsible for net acid excretion and final adjustments of the acid-base homeostasis. Cultured collecting duct cells (mOMCD1), which express GPR4 mRNA endogenously, exhibit pH-dependent accumulation of intra- Blood samples were obtained from the tail artery in conscious mice.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Several investigators have demonstrated that GPR4 (G protein-coupled receptor 4), 4,8,9 OGR1 (ovarian cancer G protein-coupled receptor 1, GPR68), 4,10 -12 and TDAG8 (T cell death-associated gene 8, GPR65) can be stimulated by a reduction in extracellular pH to induce second messenger generation. [13][14][15][16] An elegant study by Ludwig et al 4 demonstrated that mutation of specific putative proton-accepting histidine residues in OGR1 significantly impaired acid-stimulated phosphoinositide generation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Baf A1 has previously been shown to arrest AQP2 in the trans-Golgi network (TGN) in LLC-PK 1 cells, a porcine cell line stably expressing AQP2. 29,30 In MCD4 cells, 4AD caused an accumulation of AQP2 in perinuclear patches ( Figure 1, A and B) resembling those in LLC-PK 1 cells that represent the TGN. 17,30 In IMCD cells, 4AD did not induce the formation of patches clearly classifiable as TGN (Figure 2A).…”
Section: Ad Increases Intravesicular Ph and Causesmentioning
confidence: 99%
“…2 (1)(2)(3)(4)(5)(6). Mutations in the vasopressin V 2 receptor and AQP2 cause congenital nephrogenic diabetes insipidus, a disease characterized by a massive loss of water through the kidney (7,8).…”
mentioning
confidence: 99%